Transaksi E-Commerce dalam Sudut Pandang Perdagangan Internasional - Amelia Amelia; Tasya Syasmita; Rini Apriyanti (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2024)
E-commerce allows cross-border transactions to occur, so the United Nations (UN) has an interest in regulating it through a body called UNCITRAL. UNCITRAL as an international organization under the United Nations (UN) supports and develops discussions regarding the development of information technology and its impact on electronic commerce. This research aims to analyze E-Commerce transactions from a sharia economic perspective. The research method used is a literature study approach. Qualitative legal research is usually known as document study, which uses secondary data as its source, such as court decisions, doctrines, regulations, legal theories or official documents, books, reports and journals regarding explaining the juridical review of E-Commerce transactions from a different perspective. sharia economics. The results of this research show that technological developments have brought changes to daily living habits, people who previously shopped in traditional markets are now switching to e-commerce because it is considered more effective, efficient and also cheaper. The impact of technological developments extends to Indonesia. This is marked by the proliferation of e-commerce businesses. In Islam, all efforts must be made in accordance with applicable legal provisions so that no group or party is harmed. Technological developments have brought changes to daily living habits, people who previously shopped in traditional markets are now switching to e-commerce because it is considered more effective, efficient and also cheaper